2018
DOI: 10.1038/s41591-018-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity and cooperativity between subclonal populations of pediatric glioblastoma and diffuse intrinsic pontine glioma cells

Abstract: The failure to develop effective therapies for pediatric glioblastoma (pGBM) and diffuse intrinsic pontine glioma (DIPG) is in part due to their intrinsic heterogeneity. We aimed to quantitatively assess the extent to which this was present in these tumors through subclonal genomic analyses and to determine whether distinct tumor subpopulations may interact to promote tumorigenesis by generating subclonal patient-derived models in vitro and in vivo. Analysis of 142 sequenced tumors revealed multiple tumor subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
176
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 57 publications
13
176
0
Order By: Relevance
“…These data raised the interesting hypothesis that pHGG tumors have a requirement on a basal level of autophagy to provide sufficient energy and metabolic precursors for their continued growth and division. These observations and hypotheses are supported by published data that glial tumors exploit low level autophagy for nutrient cycling, whereas healthy brain tissues do not . This proposed reliance on basal autophagy represents an important therapeutic vulnerability, and a possible route to sensitizing glioma cells to therapeutic interventions.…”
Section: Autophagy Protein Expression In Phgg Patientssupporting
confidence: 61%
“…These data raised the interesting hypothesis that pHGG tumors have a requirement on a basal level of autophagy to provide sufficient energy and metabolic precursors for their continued growth and division. These observations and hypotheses are supported by published data that glial tumors exploit low level autophagy for nutrient cycling, whereas healthy brain tissues do not . This proposed reliance on basal autophagy represents an important therapeutic vulnerability, and a possible route to sensitizing glioma cells to therapeutic interventions.…”
Section: Autophagy Protein Expression In Phgg Patientssupporting
confidence: 61%
“…It is likely that such ancestor clones may become extinct during the progression of the tumor and are no longer detectable, a phenomenon which was described during the evolution of another highly heterogeneous tumor, the glioblastoma. 44 Finally, we would like to propose a model for the pathogenesis of MF that accounts for the previously found clonotypic heterogeneity [19][20][21] and the ITH described here (Fig 7) . ITH is readily detectable in ESP, which testifies to the history of mutational tumor evolution before seeding of neoplastic cells in the skin.…”
Section: Discussionmentioning
confidence: 72%
“…However, it is worthwhile to mention here that even subclonal mutations may present with drug targeting opportunities if the given subclone is important for the progression of the entire tumor. Cooperativity between distinct subclones was described for some metastasizing tumors [42][43][44] , and it was proposed that disruption of clonal cooperation might be an interesting therapeutic approach. Especially the targeting of Wnt and Hedgehog seems to be promising 42 , the pathway which we show here to be frequently mutated in MF (genes MACF1 , PTCH1 , RNF43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in mouse models and in Drosophila have demonstrated that subpopulations of cells can cooperate to induce tumor growth [7][8][9] and metastasis [10][11][12][13][14][15] . In diffuse intrinsic pontine glioma, Vinci and colleagues 16 identified a cooperative mechanism between H4K20 methyltransferase-wild-type and -mutant subpopulations that promotes invasion. In all of the aforementioned studies, either specific tumor subpopulations with pre-defined markers or genetically-engineered subclonal populations were examined.…”
Section: Introductionmentioning
confidence: 99%